2023
DOI: 10.1001/jamanetworkopen.2023.49659
|View full text |Cite
|
Sign up to set email alerts
|

Brain Health After COVID-19, Pneumonia, Myocardial Infarction, or Critical Illness

Costanza Peinkhofer,
Pardis Zarifkar,
Rune Haubo B. Christensen
et al.

Abstract: ImportanceBrain health is most likely compromised after hospitalization for COVID-19; however, long-term prospective investigations with matched control cohorts and face-to-face assessments are lacking.ObjectiveTo assess whether long-term cognitive, psychiatric, or neurological complications among patients hospitalized for COVID-19 differ from those among patients hospitalized for other medical conditions of similar severity and from healthy controls.Design, Setting, and ParticipantsThis prospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The presence of anxiety is associated with postpartum depression during the COVID-19 period [ 15 ]. These findings underscore the importance of addressing anxiety as a public health issue previously, particularly considering its potentially greater impact on specific populations [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The presence of anxiety is associated with postpartum depression during the COVID-19 period [ 15 ]. These findings underscore the importance of addressing anxiety as a public health issue previously, particularly considering its potentially greater impact on specific populations [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 87%
“…Anxiety, recognized as a global health issue, is estimated to have caused 44.5 million (30.2 to 62.5) disability-adjusted life years (DALYs) worldwide in 2020 [ 10 ]. Higher levels of anxiety have been reported among hospitalized patients, with those admitted due to COVID-19 exhibiting higher anxiety scores compared to those hospitalized for myocardial infarction, pneumonia, and intensive care stays [ 12 ]. In this study, anxiety levels were found to be higher in all patients hospitalized due to COVID-19 compared to healthy volunteers, and they were also higher in patients hospitalized for COVID-19 compared to those admitted for other diseases.…”
Section: Discussionmentioning
confidence: 99%